How to solve the price puzzle? A meta-analysis - Marek Rusnák; Tomáš Havránek; Roman Horváth (Charles University in Prague, Institute of Economic Studies (IES), 2011)
The short-run increase in prices following an unexpected tightening of monetary policy represents a frequently reported puzzle. Yet the puzzle is easy to explain away when all published models are quantitatively reviewed. We collect and examine about 1,000 point estimates of impulse responses from 70 articles using vector autoregressive models to study monetary transmission in various countries. We find some evidence of publication selection against the price puzzle in the literature, but our results also suggest that the reported puzzle is mostly caused by model misspecifications. Finally, the long-run response of prices to monetary policy shocks depends on the characteristics of the economy.
Keywords: C83; E52; 330; Monetary policy transmission; Price puzzle; Meta-analysis; Publication selection bias